Earthquake Damage Assessment in the Traditional Town of Sankhu, Kathmandu - Shrestha, Sudha; Bajracharya, Ashim R.; Bajracharya, Luna; Shrestha, Nisha; Maharjan, Monika (Journal of the Institute of Engineering, 2017)
Nepal Earthquakes 2015 April and may caused huge loss of lives and properties in the country. Several traditional buildings and monuments in the Kathmandu Valley were literally collapsed to the ground, completely changing the built form of several traditional towns such as Bungamati, Khokana, and Lubhu. In this regards, traditional town Sankhu is also not in an exception. According to the field survey, 90% of traditional houses were severely damaged in Sankhu. In this respect, this study was focused on rebuilding of Sankhu, preserving its traditional form and analyzing it from economic perspective. The study was based on household survey and the respondents were selected as per their availability and willingness to participate in the research process. The traditional building construction technology is rich in terms of resilience against earthquakes, if it is well maintained. Maintenance and repair of building elements of traditional building is relatively simple, without affecting the building structure and other building elements, as compared to RCC structure. Sankhu is economically struggling town and, it is very important to rebuild the town in traditional style to bring back its original identity for its prosperity in trade and tourism. It is an opportunity to bring some of the lost glory of the past and its outstanding building and monuments. Journal of the Institute of Engineering, 2016, 12(1): 27-38